Fish assemblages on fringing reefs in the southern Caribbean: biodiversity, biomass and feeding types - Jahson B. Alemu I. (Revista de Biología Tropical, 2014)
Reef fish assemblages in the Caribbean are under increasing pressure from human activities. Inadequate enforcement of legislation coupled with unreliable and data-poor landings in Tobago have led to the unregulated exploitation of reef fish for decades. This study addresses the lack of data on major reefs. Visual observations of fish fauna were conducted from November 2011-May 2013 at open access reef sites (Speyside, Charlotteville, Culloden, Arnos Vale, Mt. Irvine, La Guira, Kilgwyn, Plymouth and Black Rock) and one protected area (Buccoo Reef Marine Park). Belt transects surveys were used to determine fish density, species diversity and abundance at the 10-15m depth contour. Fish sizes were converted to biomass using the length-weight relationship of fish W=aLb. Most fish assemblages were dominated by small herbivores (<15cm), in particular Pomacentridae and Scaridae. Few large predators (>40cm) e.g. Serranidae, were noted, which is indicative of fishing pressure. MDS ordination identified three fish assemblages: i) northeastern, ii) southwestern and iii) intermediate. The northwestern cluster (Speyside and Charlotteville) were most representative of reef fish assemblages across the entire island, and exhibited the highest species richness, diversity and biomass. However, the southwestern cluster the highest numerical abundance. The marine protected area contained higher fish biomass, abundance, diversity and richness, but it was only representative of reef fish assemblages on the southwest of the island and not the entire Tobago. Research on the reef fishery, particularly spear fishing, is recommended to determine impact.